TVT‐O for treatment of pure urodynamic stress urinary incontinence: Efficacy and adverse effects at 13‐years follow‐up. Issue 5 (13th April 2020) - Serati, Maurizio; Braga, Andrea; Caccia, Giorgio; Torella, Marco; Ghezzi, Fabio; Salvatore, Stefano; Athanasiou, Stavros
Abstract: Aim: To assess the efficacy and safety of tension‐free vaginal tape‐obturator (TVT‐O) 13 years after implantation for the treatment of female pure stress urinary incontinence (SUI). This is the longest‐term evaluation available of TVT‐O outcomes. Methods: A multicenter, prospective study was conducted in five tertiary referral centers in three countries. All consecutive women with urodynamically proven pure SUI treated by TVT‐O were included. Data regarding subjective outcomes (International Consultation on Incontinence Questionnaire‐Short Form, Patient Global Impression of Improvement, and patient satisfaction scores), objective cure (stress test) rates, and adverse events were collected during follow‐up. Univariable and multivariate analyses was performed to investigate outcomes. Results: One hundred sixty‐eight women had TVT‐O implantation. At 13 year after surgery, 150 of 157 patients (95%) declared themselves cured ( P = .8). Similarly, at 10‐year evaluation, 148 of 160 patients (92%) were objectively cured. No significant deterioration of objective cure rates was observed over time ( P = .1). The multivariate analysis showed that previous anti‐incontinence procedures and obesity independently predicted the subjective (odd ratio [OR]: 6.2 [95% confidence interval [CI], 1.8‐13.6]; P = .02 and OR, 1.8 [95% CI, 1.3‐3.0]; P = .03, respectively) and objective failure of TVT‐O (OR, 5.8 [95% CI, 1.6‐13.2]; P = .02 and OR, 1.6 [95% CI, 1.2‐3.2]; P = .03, respectively). We found four cases of sling exposure; all of them occurred after the 10‐year follow‐up. Conclusions: The 13‐year results of this study showed that TVT‐O is a highly effective and safe option for the treatment of SUI. We found that there is a significantly higher risk of having a sling exposure over 10 years after the procedure; however, the incidence is very low.